The role of ZC3H13 in promoting M2 macrophage infiltration via m6A methylation in esophageal squamous cell carcinoma tumor progression - Yan, Qihang; Xu, Chendi; Gong, Li; Liang, Dachuan; Yang, Jie; Zheng, Yuzhen; Wang, Junye (Frontiers in Immunology, 2025)
IntroductionZC3H13 (zinc finger CCCH-type containing 13) is a member of the zinc finger protein family with regulatory roles in gene expression and represents a crucial m6A methyltransferase. However, the precise function of ZC3H13 in the esophageal squamous cell carcinoma tumor microenvironment (TME) remains incompletely understood. Our study primarily investigated the impact of ZC3H13 on m6A methylation modification in ESCC and explored the roles of ZC3H13 and M2 macrophages in ESCC.MethodsWe employed bioinformatics analysis to assess the function of ZC3H13 in ESCC. Quantification of ZC3H13, CCL5, CXCL8, and macrophage infiltration in clinical samples and cell line-derived xenograft (CDX) tumor models was conducted using real-time quantitative PCR (qRT-PCR), western blot (WB), immunohistochemistry (IHC), Immunofluorescence (IF), and Enzyme-linked immunosorbent assay (ELISA). The colorimetric method was utilized to detect m6A methylation in cells and tissues. Tumor proliferation, migration, and invasion were evaluated using CCK8, EdU staining, colony formation tests, transwell assays, and CDX models.ResultsWe found that elevated ZC3H13 expression was positively correlated with m6A methylation modification in ESCC tumor tissue. ZC3H13 mutation led to abnormal nuclear metastasis of METTL14 and METTL3. Silencing ZC3H13 inhibited ESCC tumor growth and M2 macrophage infiltration in mice. ZC3H13 silencing also suppressed the expression of CCL5 and CXCL8 mRNA. M6A modification enhanced the stability of CXCL8 mRNA. ESCC tumors promoted the polarization of M0-M2 macrophages through the CXCL8-CXCR2 axis, which CXCR2 inhibitors or anti-CXCL8 antibodies could inhibit. Migration of M0 macrophages was facilitated by CCL5.DiscussionOur findings elucidate the connection between ZC3H13-mediated m6A modification and M2 macrophage infiltration in the ESCC-TME, resulting in M2 macrophage polarization and increased M2 macrophage infiltration.